Study of distance range visual measurement in the new Depth From Defocus method - Murawski, Krzysztof; Arciuch, Artur; Pustelny, Tadeusz (Photonics Letters of Poland, 2016)
The article presents results achieved during researching the distance measuring method belonging to Depth From Defocus techniques. The method has been developed to determine the shape of the flaccid diaphragm used in the Ventricular Assist Device (VAD). The shape is determined on the basis of distance measured between the CCD sensor plate of the camera and markers located on the flaccid diaphragm. The goal of this paper is to present the influence of the size of the marker on the distance range measured between the camera and diaphragm used in the pneumatic prosthetic heart. Full Text: PDF References K. Murawski, "Method of Measuring the Distance to an Object Based on One Shot Obtained from a Motionless Camera with a Fixed-Focus Lens", Acta Phys. Pol. A 127 (6), 1591 – 1595 (2015). CrossRef K. Murawski, Method of measuring the distance using the cameras, Patent Application No. P.408076 (2014) - in Polish. H. Wang, J. Hu, "Active stereo method for three-dimensional shape measurement", Optical Engineering 51 (6), 1 – 8 (2012). CrossRef SY. Chen, YF. Li, "Finding Optimal Focusing Distance and Edge Blur Distribution for Weakly Calibrated 3-D Vision", IEEE Transactions on Industrial Informatics 9 (3), 1680-1687 (2013). CrossRef F. Bonin-Font, A. Burguera, A. Ortiz, G. Oliver, "A monocular mobile robot reactive navigation approach based on the inverse perspective transformation", ROBOTICA 31, 225 – 249 (2013). CrossRef A. Bourdonnaye, R. Doskočil, V. Křivánek, A. Štefek, "Practical Experience with Distance Measurement Based on Single Visual Camera", Advances in Military Technology 7 (2), 49 – 56 (2012). DirectLink http://tdserver1.fnal.gov/darve/mu_cool/pressuretest/Basics_of_Photogrammetry.pdf, (2015). DirectLink K. Yue, Z. Li, M. Zhang, S. Chen, "Transient full-field vibration measurement using spectroscopical stereo photogrammetry", OPTICS EXPRESS 18 (26), 26866 – 26871 (2010). CrossRef Y. Morimoto, A. Masaya, M. Fujigaki, D. Asai, "Shape Measurement by Phase-Stepping Method Using Multi-Line LEDs", Applied Measurement Systems, 7, 137 (2012). CrossRef R. B. Rusu, A. Aldoma, S. Gedikli, M. Dixon, Tutorial at IEEE/ RSJ International Conference on Intelligent Robots and Systems (IROS), (2011). A. Saxena, H. Koppula, R. Newcombe, X. Ren, Workshop in conjunction with Robotics: Science and Systems (RSS), (2013). J. Sarna, R. Kustosz, E. Woźniewska, M. Gonsior, A. Jarosz, K. Szymańska, D. Hansel, E. Krzak, Program „Polskie Sztuczne Serce” Sojusz Medycyny, Nauki i Techniki, Epigraf s.c., Zabrze, 1 – 240 (2013). DirectLink P. Gibinski, G. Konieczny, E. Maciak, Z. Opilski, T. Pustelny, Acoustic device for measuring instantaneous blood volume in cardiac support chamber i.e. pneumatic heart assist driving chamber, has sensor supporting heart in openings, and audio amplifier connected with volume unit of blood-cell support, Patent No. PL394074-A1. K. Murawski, T. Pustelny, M. Murawska, System and method of determining the shape of diaphragm of pneumatic extracorporeal heart assist pump, Patent Application No. P.414104, (2015) - in Polish. K. Różanowski, K. Murawski, "An Infrared Sensor for Eye Tracking in a Harsh Car Environment", Acta Phys. Pol. A 122 (5), 874 – 879 (2012). CrossRef K. Murawski, D. Białas, M. Rękas, "Measurement of Corneal Neovascularisation with the Use of Image Processing Techniques", Acta Phys. Pol. A 127 (6), 1732 – 1736 (2015). CrossRef